2011
DOI: 10.1161/circulationaha.110.980151
|View full text |Cite
|
Sign up to set email alerts
|

Low Prevalence of “Ideal Cardiovascular Health” in a Community-Based Population

Abstract: Background-Cardiovascular health is a new construct defined by the American Heart Association (AHA) as part of its 2020 Impact Goal definition. The applicability of this construct to community-based populations and the distributions of its components by race and sex have not been reported. Methods and Results-The AHA construct of cardiovascular health and the AHA ideal health behaviors index and ideal health factors index were evaluated among 1933 participants (mean age 59 years; 44% blacks; 66% women) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
113
8
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(141 citation statements)
references
References 28 publications
17
113
8
3
Order By: Relevance
“…Our findings of poor performance on cardiovascular health metrics are similar to several studies in different populations, including Northern Manhattan; Forsyth County, North Carolina; Jackson, Mississippi; Washington County, Maryland; Minneapolis, Minnesota; and Allegheny County, Pennsylvania 9, 10, 11, 12. Recent analyses have similarly demonstrated marked reductions in mortality5, 13, 14, 19 and 20‐year fatal and nonfatal CVD event rates10 with higher cardiovascular health scores.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our findings of poor performance on cardiovascular health metrics are similar to several studies in different populations, including Northern Manhattan; Forsyth County, North Carolina; Jackson, Mississippi; Washington County, Maryland; Minneapolis, Minnesota; and Allegheny County, Pennsylvania 9, 10, 11, 12. Recent analyses have similarly demonstrated marked reductions in mortality5, 13, 14, 19 and 20‐year fatal and nonfatal CVD event rates10 with higher cardiovascular health scores.…”
Section: Discussionsupporting
confidence: 87%
“…Less than 2% of the US population meets all 7 cardiovascular health metrics 9, 10, 11, 12. Published studies of populations generally free of a history of symptomatic cardiovascular events show that individuals who meet a higher number of Life's Simple 7 health metrics tend to have lower cardiovascular and all‐cause mortality13, 14; however, the impact of meeting these health metrics on long‐term survival after a stroke is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Three quarters of participants met only 1 or 2 ideal CVH metrics goals. Previous studies have reported lower prevalence values especially for persons with 1 or 2 ideal CVH metrics 7, 25, 26, 27. Folsom et al, using data from the ARIC study,9 reported that around 54% of black men and 55% of black women had between 1 and 2 ideal CVH metrics.…”
Section: Discussionmentioning
confidence: 97%
“…Fewer Americans, particularly blacks, achieve ideal CVH, especially for BMI, physical activity, and healthy diet, which have been strongly associated with incident diabetes mellitus 7, 8, 9. The association between AHA‐defined ideal CVH and the development of diabetes mellitus is less clear among blacks than among other race‐ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…Although studies have convincingly demonstrated the health benefits of the ideal CVH construct, prevalence of ideal CVH metrics has consistently been low in community samples [17], longitudinal cohort studies [10,18], and nationally representative surveys [11•, 12, 19]. Longitudinal analyses of multiple NHANES surveys demonstrated prevalence of ideal CVH of less than 2 % that remained similarly low over time [11•].…”
Section: Prevalence Of Cardiovascular Health In the Usamentioning
confidence: 99%